2014
DOI: 10.1016/j.molcel.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Specific Recognition of Bacterial Ligands by NAIP/NLRC4 Inflammasomes

Abstract: SUMMARY NLR (nucleotide-binding domain [NBD]- and leucine-rich repeat [LRR]-containing) proteins mediate innate immune sensing of pathogens in mammals and plants. How NLRs detect their cognate stimuli remains poorly understood. Here, we analyzed ligand recognition by NAIP (NLR Apoptosis Inhibitory Protein) inflammasomes. Mice express multiple highly related NAIP paralogs that recognize distinct bacterial proteins. We analyzed a panel of 43 chimeric NAIPs, allowing us to map the NAIP domain responsible for spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
170
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(177 citation statements)
references
References 41 publications
4
170
1
2
Order By: Relevance
“…Yet, how NAIPs recognized their ligands remained unknown. As mentioned earlier, mice have several NAIPs with high diversity among different inbred strains [25]. Exploiting this high variability, an extensive mutagenesis study of more than 40 chimeric proteins enabled the mapping of the parts of the NAIP molecules responsible for the recognition of and response to bacterial components (Fig.…”
Section: Initial Recognition Of Pamps Is Mediated By Naipsmentioning
confidence: 96%
See 3 more Smart Citations
“…Yet, how NAIPs recognized their ligands remained unknown. As mentioned earlier, mice have several NAIPs with high diversity among different inbred strains [25]. Exploiting this high variability, an extensive mutagenesis study of more than 40 chimeric proteins enabled the mapping of the parts of the NAIP molecules responsible for the recognition of and response to bacterial components (Fig.…”
Section: Initial Recognition Of Pamps Is Mediated By Naipsmentioning
confidence: 96%
“…Exploiting this high variability, an extensive mutagenesis study of more than 40 chimeric proteins enabled the mapping of the parts of the NAIP molecules responsible for the recognition of and response to bacterial components (Fig. 1D) [25]. Switching segments between points, mostly located within regions of high sequence identity among NAIPs, enabled the mapping of the PAMP specificity domain to regions comprising of HD1, WHD, and HD2 and the unannotated segment between HD2 and LRR of NAIP5 for flagellin, and HD1, WHD, and HD2 of NAIP2 for the rod protein of T3SS (Fig.…”
Section: Initial Recognition Of Pamps Is Mediated By Naipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work showed that the NOD domain of NAIPs confers ligand binding and specificity [10], yet according to the new studies the same domain also forms the nucleating surface that initiates complex assembly. Since thus far the structure of inactive or activated NAIPs has not been reported, the structural basis underlying ligand-NOD domain interaction is unknown and the resulting conformational changes remain to determined.…”
mentioning
confidence: 97%